Buparlisib in combination with tamoxifen in pretreated patients with hormone receptor‐positive, HER2‐negative advanced breast cancer molecularly stratified for PIK3CA mutations and loss of PTEN expression. (30th April 2020) - Welt, Anja; Wiesweg, Marcel; Theurer, Sarah; Abenhardt, Wolfgang; Groschek, Matthias; Müller, Lothar; Schröder, Jan; Tewes, Mitra; Chiabudini, Marco; Potthoff, Karin; Bankfalvi, Agnes; Marschner, Norbert; et al.
Abstract: The PIKTAM study evaluated the efficacy and safety of the PI3K inhibitor buparlisib in combination with tamoxifen in hormone receptor‐positive (HR + ), HER2‐negative advanced breast cancer patients after failure of prior endocrine therapy. In this open‐label, single‐arm phase II trial, 25 patients were enrolled in 11 sites in Germany. Patients were stratified according to PIK3CA mutation status (tissue and cfDNA from serum samples) and/or loss of PTEN expression. Patients received buparlisib (100 mg) and tamoxifen (20 mg) once daily on a continuous schedule (28‐day cycle) until progression or unacceptable toxicity. Primary endpoint was overall 6‐month progression‐free survival (PFS) rate. Key secondary endpoints included the 6‐month PFS rate in subpopulations, PFS, overall survival, overall response rate (ORR), disease control rate (DCR), and safety. Overall, the 6‐month PFS rate was 33.3% (n/N = 7/21, one‐sided 95% CI 16.8‐100) and median PFS was 6.1 (CI 2.6‐10.6) months. The ORR and DCR were 12.5% and 44%. The PIK3CA ‐mutated subgroup consistently showed the highest 6‐month PFS rate (62.5%, n/N = 5/8), median PFS (8.7 months), ORR (40%), and DCR (80%). No new safety signals emerged. Most common adverse events were gastrointestinal disorders (56%), psychiatric/mood disorders (48%), skin rash/hypersensitivity (44%), cardiovascular (40%), and hepatic (32%) events. The trial was prematurely terminated due to the substantially altered risk‐benefit profile of buparlisib. Nevertheless, PIK3CA mutations emerged as a clinically feasible and useful biomarker for combined PI3K inhibition and endocrine therapy in patients with HR + breast cancer. Further biomarker‐stratified studies with isoform‐specific PI3K inhibitors are warranted. EudraCT No: 2014‐000599‐24. Abstract : This phase II study evaluated the efficacy and safety of buparlisib plus tamoxifen in pretreated patients with advanced HR + /HER2 − breast cancer, stratified for PIK3CA mutations and/or loss of PTEN expression in tumor tissue and circulating blood DNA. A signal for higher buparlisib/tamoxifen activity in patients with PIK3CA‐mutated tumors was obtained. Our findings support the value of somatic PIK3CA mutations as predictive biomarker for PI3K‐targeting therapies combined with antihormonal treatment in metastatic HR + breast cancer.